MCMICRO: a scalable, modular image-processing pipeline for multiplexed tissue imaging - Schapiro, Denis; Sokolov, Artem; Yapp, Clarence; Chen, Yu-An; Muhlich, Jeremy L.; Hess, Joshua; Creason, Allison L.; Nirmal, Ajit J.; Baker, Gregory J.; Nariya, Maulik K.; Lin, Jia-Ren; Maliga, Zoltan; et al. (Nature methods, 2022)
Highly multiplexed tissue imaging makes detailed molecular analysis of single cells possible in a preserved spatial context. However, reproducible analysis of large multichannel images poses a substantial computational challenge. Here, we describe a modular and open-source computational pipeline, MCMICRO, for performing the sequential steps needed to transform whole-slide images into single-cell data. We demonstrate the use of MCMICRO on tissue and tumor images acquired using multiple imaging platforms, thereby providing a solid foundation for the continued development of tissue imaging software.
Gesehen am 01.06.2022
First published online: 25 November 2021